Application of wavelet analysis and its interpretation in rotating machines monitoring and fault diagnosis. A review - Abouelanouar, Bouchra; Elamrani, Mostafa; Elkihel, Bachir; Delaunois, Fabienne (International Journal of Engineering and Technology, 2018)
Vibration analysis is a key element of predictive maintenance of rotating machines. Several signal analysis methods are used to obtain useful information from vibration signatures. This signal highlights the changes in time domain (root mean square), in the frequency spectrum (Fourier Transform) and in the time-frequency (Short Time Fourier Transform and Wavelet Transform). Currently, the most of these methods use spectral analysis based on Fourier Transform (FT). However, these methods exhibit some limitations: it is the case of non-stationary signals.